Current trends, Development and Applications of Analytical and Bioanalytical Techniques - A review - Gurmeet S. Chhabra, (International Journal of Pharma and Bio Sciences, 2021)
Drug development plays a key role in curing the diseases and improving human health. The pharmaceutical product need to maintain the quality, free from various possible degradants, possible contaminants and to be administered in a proper amount to provide the therapeutic effect. These drugs may develop impurities at various levels from its development to storage, which creates a risk for its administration. The need of an hour is to evolve a systematic approach and to develop well-designed, hyphenated and advanced instrumental techniques for the purpose of drug estimations. The advancement of analytical and bioanalytical techniques with enough accuracy, selectivity, sensitivity, speed, robustness, resolution, use of solvents, cost factors etc is thus bringing a new era of development which will serve as a rapid and unambiguous tool for the estimation and quantitation of drugs. This advancement in technique is also applicable for environmental analysis, food analysis, plant analysis, insecticides, nutraceuticals and other bioactive compounds hereby setting up quality standards and specifications for seeking the regulatory authorities approval. The purpose of this review is to highlight a variety of recent and advanced extraction, analytical and bioanalytical techniques, their corresponding principles and applications that are used in the analysis of not only the synthetic drugs, but also for the quantitative and qualitative evaluation of herbal medicines and its formulations.